Effect of NPK fertilizer and biochar application to soil chemical properties of irrigation paddy - . Sufardi; Khairun Nisa; . Zaitun; . Chairunas; Anischan Gani; Peter Slavich; Malem McLeod (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The objective of experiment was to know effect of NPK and Biochar application to soil chemical properties of paddy rice. The research was conducted in Empetrieng village, Aceh Besar district, Aceh Province, Indonesia.  The experimental arranged in a randomized complate block design with two factor and four replication.  First factor was NPK 15:15:15 fertilizer application (0 kg ha-1; 60 kg ha-1; and 120 kg ha-1) and second factor was Biochar application (0 ton ha-1; and 10 ton ha-1).  The result showed that : (1) application of Biochar affected significanly to soil pH; (2) application of NPK fertilizer affected significanly to K in soil; and 3) interaction of Biochar and NPK fertilizer application affected significantly to pH and P in soil